Taller educativo SIAGIE para la mejora de la gestión administrativa del directivo en cinco instituciones educativas públicas urbanas nivel secundario Iquitos 2023 - Ribeiro Cuttin Aida Luz (2025)
The purpose of this research was to determine whether the implementation of this workshop results in a significant improvement in the administrative management of school principals, while optimizing school processes. A pre experimental, single-group design with pretest and posttest was used. Initially, the level of administrative management each principal possessed was assessed. Subsequently, an intensive workshop was conducted to train principals in the practical use of SIAGIE. Finally, a standardized instrument was reapplied to measure the different indicators before and after the training. The findings demonstrate a significant improvement, as principals in the posttest showed higher performance in administrative management using SIAGIE, facilitating the organization of enrollments, attendance tracking, and the generation of academic records and reports. These results indicate that the training fosters greater digital and administrative competencies, enabling the systematization and enhancement of institutional processes. In other words, the SIAGIE educational workshop is effective, as it improves administrative management, promoting more efficient and transparent school governance. The research highlights the importance of this tool and proposes replicating similar training programs to enhance the quality of educational administration.